Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1159/000468156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Types during the First Months of Life on Calciuria Levels in Healthy Infants: A Secondary Analysis from a Randomized Clinical Trial

Abstract: Background/Aims: Dietary factors can modify calciuria. We aim to investigate urinary calcium excretion in healthy infants according to their protein. Methods: Secondary data analysis from a randomized clinical trial where healthy term infants were randomized after birth to a higher (HP) or lower (LP) protein content formula that was consumed until age 1 year. A non-randomized group of breastfed (BF) infants was used for reference. Anthropometry, dietary intakes and calciuria (calcium/creatinine ratios) from sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…This agree with the prospective randomized clinical trial performed by Ferré et al, [17] which showed that the high protein formulation significantly increased the urinary Ca/Cr ratio, according to this study [17] . Consistent with our research, Cillo et al, [18] who performed a study on 104 healthy newborns had found that neonates that were exclusively fed artificial milk exhibited a significantly higher urinary excretion of Ca (mean 0.10±0.06) compared to those that were exclusively fed breast milk [18] . Our results comes in harmony with the study obtained by Erol et al [19] Using 425 healthy children aged 0-5 years, this study aimed to establish age-specific reference values for UCa/Cr in healthy Turkish children and examine the effect of nutrition on UCa excretion in infants younger than six months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agree with the prospective randomized clinical trial performed by Ferré et al, [17] which showed that the high protein formulation significantly increased the urinary Ca/Cr ratio, according to this study [17] . Consistent with our research, Cillo et al, [18] who performed a study on 104 healthy newborns had found that neonates that were exclusively fed artificial milk exhibited a significantly higher urinary excretion of Ca (mean 0.10±0.06) compared to those that were exclusively fed breast milk [18] . Our results comes in harmony with the study obtained by Erol et al [19] Using 425 healthy children aged 0-5 years, this study aimed to establish age-specific reference values for UCa/Cr in healthy Turkish children and examine the effect of nutrition on UCa excretion in infants younger than six months.…”
Section: Discussionsupporting
confidence: 92%
“…This agree with the study obtained by Gül et al [26] to determine the prevalence of hypercalciuria and percentiles of urinary calcium excretion among school-aged children in Tokat [23] . However, the study obtained by Cillo et al [18] showed higher Ca excretion in newborns with a body weight less than 3 kg than those with body weight more than 3 Kg [18] .…”
Section: Discussionmentioning
confidence: 87%
“…Diet is a major factor influencing urinary Ca excretion which promotes hypercalciuria and can lead to nephrocalcinosis (Khan, 2010). A randomized study including 1,090 healthy term infants from five different countries reported hypercalciuria prevalence in 16.8% of infants fed a high protein formula (2.05 to 3.20 g/100 mL) compared to 4.9% of infants fed a low protein formula (1.25 to 1.60 g/100 mL) for 3 months (Ferré et al., 2017).…”
Section: Resultsmentioning
confidence: 99%